2014
DOI: 10.2174/1874434601408010048
|View full text |Cite
|
Sign up to set email alerts
|

The Well-Being of Relatives of Patients with Atrial Fibrillation: A Critical Incident Technique Analysis

Abstract: Background: The well-being of relatives of patients having chronic heart diseases (CHD) has been found to be negatively affected by the patient’s condition. Studies examining relatives of patients with atrial fibrillation (AF) indicate that their well-being may be affected in a similar manner, but further research is needed. Aim: To explore and describe critical incidents in which relatives of patients experience how AF affects their well-being and what actions they take to handle these situations. Design an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 38 publications
1
16
0
Order By: Relevance
“…, Ekblad et al . ). This is consistent with the findings of the present study, which revealed that couples with AF expressed causative factors to explain the trajectory of AF, such as heredity and previous lifestyle/activities.…”
Section: Discussionmentioning
confidence: 97%
“…, Ekblad et al . ). This is consistent with the findings of the present study, which revealed that couples with AF expressed causative factors to explain the trajectory of AF, such as heredity and previous lifestyle/activities.…”
Section: Discussionmentioning
confidence: 97%
“…Likewise, Ekblad et al. () also described the relatives of patients with AF being worried about the patient's health and anxiety when they engaged in activities that demanded physical exertion. This was based on their beliefs that exertion damaged the heart (Ekblad et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…| 151 describe that living with AF not only affect the sufferers but also affects the well-being of the partner or close relatives (Bohnen et al, 2011;Dalteg, Benzein, Sandgren, Fridlund, & Malm, 2014;Ekblad, Malm, Fridlund, Conlon, & Rönning, 2014). Social coping support can also be lacking (McCabe, Schumacher, et al, 2011).…”
Section: Bergtun Et Almentioning
confidence: 99%
See 2 more Smart Citations